Health-Related Quality of Life in Patients With ANCA-Associated Vasculitis and Sinonasal Involvement: A Single-Center Cross-Sectional Study. Issue 1 (2nd November 2020) - Cazzador, Diego; Padoan, Roberto; Colangeli, Roberta; Pendolino, Alfonso Luca; Felicetti, Mara; Zanoletti, Elisabetta; Emanuelli, Enzo; Martini, Alessandro; Doria, Andrea; Nicolai, Piero; Schiavon, Franco
Abstract : Background/Objective: The aim of this study was to assess the impact of sinonasal morbidity on quality of life (QoL) in antineutrophil cytoplasmic antibody–associated vasculitis (AAV). Methods: This cross-sectional case-control study enrolled 71 patients—44 AAV cases with (ear, nose, and throat [ENT]–AAV) or without ENT involvement (non–ENT-AAV) undergoing multidisciplinary evaluations and 27 chronic rhinosinusitis (CRS) cases. Three validated QoL questionnaires (Sino-Nasal Outcomes Test-22 [SNOT-22], Nasal Obstruction Symptom Evaluation [NOSE], and Short-Form 36) were administered, and the 3 groups were compared. Results: The ENT-AAV patients were significantly younger ( p = 0.01), with less antineutrophil cytoplasmic antibody positivity frequency ( p = 0.035) and lower renal involvement ( p = 0.003) than the non–ENT-AAV patients. The SNOT-22 questionnaire demonstrated significantly greater sinonasal morbidity in ENT-AAV patients compared with CRS patients ( p < 0.001). The NOSE score of ENT-AAV patients was comparable to those of CRS patients, but higher than that of non–ENT-AAV patients ( p < 0.001). The SNOT-22 and NOSE scores positively correlated with disease activity ( p = 0.037; p = 0.004, respectively). Short-Form 36 domain-by-domain analysis revealed a significantly poorer QoL in ENT-AAV patients, especially with physical functioning being progressively impaired in CRS, non–ENT-AAV, and ENT-AAV patients ( p < 0.001). No significant differences in QoL came to light when AAV patients were stratified according to current systemic o local treatments. Conclusions: The QoL in AAV patients is significantly reduced, especially in the presence of ENT involvement. The AAV-related nasal morbidity is consistent and comparable to that reported by CRS patients. It significantly affects patients' QoL and in particular social functioning, leading to limitation in daily/work activities. Organ-focused questionnaires and multidisciplinary management are warranted to pursue a treat-to-target approach in these patients.